Pengembangan Bahan Ajar IPA Berbasis Literasi Sains Pada Materi Reproduksi Tumbuhan - Anita Anita; Maya Istyadji; Sauqina Sauqina (Pusat Riset dan Inovasi Nasional, 2024)
The low degree of scientific literacy in Indonesia serves as the driving force for this research. As a result, efforts are being made to conduct research and develop scientific literacy-based science teaching resources. The purpose of this study is to evaluate the efficacy of scientific literacy-based science teaching materials on plant reproduction in academic settings. The process of research and development (R&D) employs a modified Four D (4D) paradigm. This research process consists of three stages: definition, design, and development. Three academic validators are included regarding the topic of this study and advancement. The scores from the product validation questionnaire are a category of numerical information obtained. In this research and development, literacy-based science teaching materials on plant reproduction were validated by expert validators to ensure that the produced products are truly valid. According to the expert validator assessment results, the scientific literacy part of the instructional material product had a validation result of 3.58 with a percentage of 89%, while the overall product received an average of 3.58. Therefore, it can be said that the instructional materials that have been generated are reliable and appropriate for use in the educational process.